2009
DOI: 10.1016/j.jtcvs.2008.08.006
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with the development of aortic valve regurgitation over time after two different techniques of valve-sparing aortic root surgery

Abstract: In regard to aortic regurgitation grade over time, patients with Marfan syndrome and a large preoperative aortic annulus diameter were better treated with the reimplantation technique, whereas those with a smaller diameter were better treated with the remodeling technique. Concomitant free-edge plication of prolapsing cusps was disadvantageous in both groups. Considering these factors may serve to improve the aortic valve longevity after valve-sparing aortic root surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
78
1
3

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(86 citation statements)
references
References 26 publications
4
78
1
3
Order By: Relevance
“…In the effort to reproduce this geometry, many valve-sparing reimplantation techniques have been proposed, including the use of the Valsalva graft. Nevertheless, despite the difficulty in obtaining the perfect reconstruction of the aortic root geometry, several groups, including ours, have achieved satisfactory results in the late evaluation of such surgeries [16][17][18].…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…In the effort to reproduce this geometry, many valve-sparing reimplantation techniques have been proposed, including the use of the Valsalva graft. Nevertheless, despite the difficulty in obtaining the perfect reconstruction of the aortic root geometry, several groups, including ours, have achieved satisfactory results in the late evaluation of such surgeries [16][17][18].…”
Section: Discussionmentioning
confidence: 78%
“…Through their study, they suggested that the remodeling technique should be used for smaller rings and the reimplantation technique for the dilated ones [20]. Reinforcing Schäfers's group's idea, Hanke et al [17] demonstrated that the recurrence of aortic regurgitation was related to three factors: Marfan's syndrome, the need for repair of one or more leaflets of the aortic valve and the diameter of the aortic ring. They showed that the remodeling technique for larger rings resulted in more regurgitation, while the reimplantation technique for smaller rings resulted in more leaflet deterioration.…”
Section: Discussionmentioning
confidence: 98%
“…At mid-term follow-up, 5-year freedom from recurrent regurgitation was encouraging at 88±5.3%. [24]. Indeed, in our recent published experience, we observed a trend towards greater recurrent regurgitation in patients who had prolapsed leaflets, which did not reach statistical significance [16] (Fig.…”
Section: Valve-sparing Root Replacement With Concomitant Valve Repairmentioning
confidence: 75%
“…Twenty-six patients had MFS and the rates of freedom from valve replacement and from AR >2+ were 100% [22]. Hanke et al from Sievers' group reported on 191 V-SARR procedures including David II remodelling and David I procedures, with 13 and 20% of patients having MFS [23]. Factors associated with the development of a significant increase in AR were MFS and preoperative aortic annulus dimension, among others.…”
Section: Results Of David I Type Of Valve-sparing Aortic Root Replacementioning
confidence: 99%